The role of the Bulgarian clergy in the development of education in the Macedonian territory at the turn of the 20th century - Znamierowska-Rakk, Elżbieta (Balcanica Posnaniensia. Acta et studia, 2010)
The article analyzes the crucial role of the Bulgarian clergy in the development of education in the Macedonian territories between the late 19th and early 20th centuries. The study’s background lies in the political context following the 1878 Treaty of Berlin, which left Macedonia and Adrianople Thrace within the Ottoman Empire, forcing Bulgarians to seek new forms of national and cultural activity within church structures. The aim of the research is to show how the educational initiatives of the Bulgarian clergy - especially under the aegis of the Bulgarian Exarchate, established in 1870 – became an instrument for shaping the national consciousness of the Macedonian Slavs. The author’s findings are based on historical sources and studies concerning the history of education, the Church, and the Bulgarian national movement in Macedonia, including Exarchate documents, Bulgarian and Macedonian literature, and works by contemporary researchers. The research method relies on comparative analysis and interpretation of narrative and statistical sources that reveal the scale of the development of Bulgarian education. The article concludes that the Bulgarian clergy played a fundamental role in awakening and consolidating the national consciousness of the Slavic population in Macedonia. Through the activities of the Exarchate, an extensive network of schools, reading rooms, and cultural institutions was established, forming the foundation of the modern national movement. Bulgarian education not only contributed to the integration of local communities around the idea of Bulgarian identity but also prepared the ground for the development of political and revolutionary activities in the region. The author emphasizes that in this process, the clergy fulfilled both religious and national-political functions, becoming one of the key factors shaping the identity of the Macedonian Slavs at the turn of the 19th and 20th centuries.